Pengaruh Pemahaman Konsep Dasar Ekonomi dan Gaya Hidup Hedonis terhadap Rasionalitas Ekonomi Siswa Kelas X SMA Negeri 4 Batanghari - Dwi Jayanti, Pitri; Arpizal, Arpizal; Sri Dwijayanti, Novia (Edu Sosial, 2023)
This study aims to determine the effect of financial attitude and reference groups either partially or simultaneously on purchasing decisions in e-commerce. This research is a research with a quantitative approach to the type of survey research. The population of this study were Students of the Social Sciences Education Department (PIPS) Class of 2020, the Teaching and Education Faculty (FKIP), Jambi University. Data collection techniques using Google from. The data analysis technique used is multiple regression analysis. The results of this study are that partially there is a positive and significant effect of financial attitude on purchasing decisions in e-commerce and there is a positive and significant influence of reference groups on purchasing decisions in e-commerce. Simultaneously there is a positive and significant effect of financial attitude and reference group on purchasing decisions Â